PENDAMPINGAN PASTORAL KONSELING BAGI REMAJA KORBAN PERCERAIAN - Taarega, Viena Bella; Tadung, Frieska Putrima (PT. Giat Konseling Nusantara, 2024)
Divorce creates a dangerous situation in the life of a teenager. Nowadays, divorce is becoming more and more common. This then affects the self-acceptance of adolescents. Many churches today only care about adults who are considered to be actors in a divorce. The church has not provided pastoral assistance to youth as victims of divorce. Divorce is a wound that can be traumatic for teenagers. Adolescence is a period of transition to early adulthood, where the development period is the most difficult to pass. Adolescence is a time of forming a person's identity, the crisis experienced when his parents divorced will have an impact on his life in the future of adolescence. Pastoral assistance aims to assist, guide, and assist adolescents who are victims of divorce to obtain healing and recovery. This study uses a qualitative research method with a case study approach.